The negative representation of female teachers on twitter related to online learning during the pandemic - Sarwono, Billy K.; Salamah, Ummi; Meilinda, Nurly (Institute for Advanced Science Social, and Sustainable Future, 2024)
This research was conducted due to a negative perception of elementary school teachers, mostly women, on Twitter as one of the social media platforms throughout the pandemic. From a media perspective, social media become important platforms for conveying confusion as well as providing solutions to parents. The research question is how netizen represents their struggle on social media, and whether there is a difference between men and women. The research used social semiotics as a method. The results are as follows. First, the conversation on female teachers' roles and responsibilities did not describe the existing social reality because the teachers’ voices were unheard in the tweets. If did exist any, their voices were conveyed by someone else. Second, men spoke in an asymmetrical style of communication and considered the problems related to online learning to be systematic. While on the other hand women used symmetrical ones which ironically discriminate against or make a scapegoat of female teachers.